2021
DOI: 10.1590/0102-311x00290120
|View full text |Cite
|
Sign up to set email alerts
|

Estimated prevalence of COVID-19 in Brazil with probabilistic bias correction

Abstract: Using data collected by the Brazilian National Household Sample Survey - COVID-19 (PNAD-COVID19) and semi-Bayesian modelling developed by Wu et al., we have estimated the effect of underreporting of COVID-19 cases in Brazil as of December 2020. The total number of infected individuals is about 3 to 8 times the number of cases reported, depending on the state. Confirmed cases are at 3.1% of the total population and our estimate of total cases is at almost 15% of the approximately 212 million Brazilians as of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, indirect comparisons with other studies may suggest a higher risk attributed to OHCWs. In Brazil, for instance, the prevalence of SARS-CoV-2 infection in the same period studied was estimated about 15% in the general population, 54 meanwhile the study by Ferreira et al 41 included in our systematic review indicated the prevalence of 22% for OHCWs. However, none of the studies included in this study examined at the potential source of infection among OHCWs, limiting the possibility of assessing the impact of occupational versus community-acquired infection.…”
Section: F I G U R E 5 Bubble Plot For Meta-regression Of Human Devel...mentioning
confidence: 75%
“…However, indirect comparisons with other studies may suggest a higher risk attributed to OHCWs. In Brazil, for instance, the prevalence of SARS-CoV-2 infection in the same period studied was estimated about 15% in the general population, 54 meanwhile the study by Ferreira et al 41 included in our systematic review indicated the prevalence of 22% for OHCWs. However, none of the studies included in this study examined at the potential source of infection among OHCWs, limiting the possibility of assessing the impact of occupational versus community-acquired infection.…”
Section: F I G U R E 5 Bubble Plot For Meta-regression Of Human Devel...mentioning
confidence: 75%
“…For example, the prevalence of anti-S IgG antibodies for SARS-CoV-2 in an extremely socioeconomic vulnerable population in Rio de Janeiro and Salvador before vaccine implementation was higher than previous estimates for these cities, indicating the significant burden of COVID-19 in these communities 10 11. The unavailability of diagnostic tools is aggravated by the arrival of new SARS-CoV-2 variants, also contributing to under-reporting of cases 8 9…”
Section: Introductionmentioning
confidence: 95%
“…In this context, testing and diagnosis are still insufficient,5 6 mainly in areas with more significant socioeconomic disadvantages, such as low-income and middle-income countries. Low-income countries’ investments in public health are often insufficient in these settings,7 leading to increase in the number of under-reported cases 8 9. For example, the prevalence of anti-S IgG antibodies for SARS-CoV-2 in an extremely socioeconomic vulnerable population in Rio de Janeiro and Salvador before vaccine implementation was higher than previous estimates for these cities, indicating the significant burden of COVID-19 in these communities 10 11.…”
Section: Introductionmentioning
confidence: 98%
“…Another important cause of hospitalisations and deaths in the last years was SARS-CoV-2. In a study performed by Figueiredo et al ,13 the estimated cases in Brazil were nearly 15% 13. Moreover, COVID-19 led to lifestyle changes by reducing physical activity performance and negative effects on healthcare access and curative and preventive quality, increasing the burden of disease and mortality after the epidemic outbreak 14.…”
Section: Introductionmentioning
confidence: 99%